2021
DOI: 10.1016/j.watres.2020.116517
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and performance of three Kenaf coagulation products under different operating conditions

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…As illustrated in Table 2, the pH values obtained are related to the type of solvent used during the extraction process. The values recorded for the zeta potential were all negative and is consistent with previous studies, which reported Hibiscus seeds as predominantly having negatively charged surfaces (Jones & Bridgeman, 2016;Okoro, Sharifi, Jesson, Bridgeman, & Moruzzi, 2021).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…As illustrated in Table 2, the pH values obtained are related to the type of solvent used during the extraction process. The values recorded for the zeta potential were all negative and is consistent with previous studies, which reported Hibiscus seeds as predominantly having negatively charged surfaces (Jones & Bridgeman, 2016;Okoro, Sharifi, Jesson, Bridgeman, & Moruzzi, 2021).…”
Section: Resultssupporting
confidence: 91%
“…KPFs with higher protein concentration gave the best removal rates indicating that the protein content in the extracts was key to the coagulation-flocculation process. Also, based on our previous work (Okoro, Sharifi, Jesson, Bridgeman, & Moruzzi, 2021), the solubilization process using salt (NaCl) improved the protein dissolution process, possibly leading to an improved polymer-particle interaction.…”
Section: Contribution Of Kenaf Protein Fraction To the Organic Matter...mentioning
confidence: 96%
See 2 more Smart Citations
“…In another research, the authors tested the effectiveness of the Moringa oleifera seeds as bio-coagulant for surface water turbidity treatment (Nhut et al 2021). Hexane, Saline and Crude were extracted from Kenaf plant seed for determining a reliable coagulation to remove organic matter (Okoro et al 2021).…”
Section: Related Researchmentioning
confidence: 99%